2019
DOI: 10.1177/1077559519835975
|View full text |Cite|
|
Sign up to set email alerts
|

The Mediating Role of Neural Activity on the Relationship Between Childhood Maltreatment and Impulsivity

Abstract: Child maltreatment is associated with a variety of risk behaviors in young adulthood; however, the underlying cognitive and neural mechanisms of this relation are not well understood. The primary aim of the present study was to examine the direct and indirect effects between maltreatment in childhood and downstream impulsivity via neural activity during a cognitive task. In a sample of emerging adult women from the rural southeastern United States, childhood abuse and neglect were assessed using the childhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…Studies investigating differences in function within, and functional connectivity between, these regions following childhood maltreatment are emerging with more recent results suggesting these changes may relate to risk for psychopathology. It was recently reported that decreased prefrontal responses during a verbal working memory task mediated the relationship between childhood maltreatment and trait impulsivity in young adult women [203]. In a study investigating functional responses to emotional faces in 182 adults with a range of anxiety symptoms, increased amygdala and decreased dorsolateral prefrontal activity to fearful and angry faces were reported-as well as increased insula to fearful and increased ventral, but decreased dorsal, anterior cingulate activity to angry faces-to mediate the relationship between childhood maltreatment and anxiety symptoms [204].…”
Section: Childhood Maltreatment and Associated Alterations In Neural mentioning
confidence: 99%
“…Studies investigating differences in function within, and functional connectivity between, these regions following childhood maltreatment are emerging with more recent results suggesting these changes may relate to risk for psychopathology. It was recently reported that decreased prefrontal responses during a verbal working memory task mediated the relationship between childhood maltreatment and trait impulsivity in young adult women [203]. In a study investigating functional responses to emotional faces in 182 adults with a range of anxiety symptoms, increased amygdala and decreased dorsolateral prefrontal activity to fearful and angry faces were reported-as well as increased insula to fearful and increased ventral, but decreased dorsal, anterior cingulate activity to angry faces-to mediate the relationship between childhood maltreatment and anxiety symptoms [204].…”
Section: Childhood Maltreatment and Associated Alterations In Neural mentioning
confidence: 99%
“…In response to threatening faces, maltreated youth exhibit a response bias compared with non-maltreated youth, as well as increased activity in ventromedial prefrontal cortex (vmPFC) and anterior cingulate cortex (ACC) when viewing fearful expressions (Hart, Lim, Mehta, Simmons, Mirza, & Rubia, 2018). Decreased PFC responses during a verbal working memory task in maltreated youth relates to trait impulsivity (Hallowell, Oshri, Liebel, Liu, Duda, Clark, & Sweet, 2019), while reduced activation in the ACC in maltreated youth relates to poorer inhibitory control during the Stroop task (Zhai, Yip, Lacadie, Sinha, Mayes, & Potenza, 2019). Maltreated youth show further evidence of impaired cognitive control with longer response times and elevated responses in the dorsal ACC, inferior PFC, and striatum when switching from prepotent to alternative responses (Mueller, Maheu, Dozier, Peloso, Mandell, & Leibenluft, 2010).…”
Section: Neural Correlates Of Elamentioning
confidence: 99%
“…The papers in this special issue represent diverse methodological approaches to studying neurobiological pathways linking child maltreatment to adjustment and psychopathology outcome across the life span. Several papers involve longitudinal data to delineate patterns over time, leading to various outcomes including alcohol use (DeBellis et al, 2019; Oshri et al, 2019), shyness (Poole, MacMillan, & Schmidt, 2018), trait impulsivity (Hallowell et al, 2019), internalizing and externalizing problems (Demers et al, 2019; Oshri et al, 2019; Peverill, Sheridan, Busso, & McLaughlin, 2019), and adaptive functioning (Demers et al, 2019). Another important aspect in the investigation of the neurobiology of child maltreatment is the concept of multilevel analysis.…”
mentioning
confidence: 99%
“…Impulsivity, the focus of the next paper (Hallowell et al, 2019), is a multifactorial construct implicated in substance use disorders (Lee, Hoppenbrouwers, & Franken, 2019) and child maltreatment (Liu, 2019). In this study, Hallowell and colleagues (2019) investigated the impact of child maltreatment on impulsivity via functional magnetic resonance imaging (fMRI) during a verbal working memory task in a sample of emerging adult females (ages 18–25 years). Higher levels of self-reported childhood maltreatment were positively associated with impulsivity, poorer working memory performance, and overall lower neural response.…”
mentioning
confidence: 99%